Recognition of ST elevation by paramedics. Issue 1 (1st January 2002) - Whitbread, M; Leah, V; Bell, T; Coats, T J
Abstract : Objective: To define the ability of UK paramedics to recognise ST segment elevation using a prehospital 12 lead electrocardiogram (ECG). Methods: Analysis of the diagnostic ability of seven paramedics 12 months after a two day training course, using interpretation of a 12 lead ECG by two cardiologists as the criterion standard. Comparison of paramedic and A&E SHO diagnosis to determine accuracy, specificity, sensitivity, negative predictive value, and positive predictive value of paramedic interpretation. Results: Paramedics showed a median accuracy of 0.95 (95% CI 0.88 to 0.98), a specificity of 0.91 (95% CI 0.53 to 1.0), a sensitivity of 0.97 (95% CI 0.94 to 0.99), a NPV of 0.77 (95% CI 0.62 to 0.92) and a PPV of 0.99 (95% CI 0.92 to 1.0). This was not significantly different from a group of experienced A&E SHOs. Conclusions: UK paramedics can recognise ST elevation using a 12 lead ECG. Radio transmission of an ECG may not be necessary to pre-alert the hospital.